Antitumor activity of vorinostat-incorporated nanoparticles against human cholangiocarcinoma cells. Issue 1 (December 2015) - Kwak, Tae; Kim, Do; Jeong, Young-Il; Kang, Dae
Abstract Background The aim of this study is to evaluate the anticancer activity of vorinostat-incorporated nanoparticles (vorinostat-NPs) against HuCC-T1 human cholangiocarcinoma cells. Vorinostat-NPs were fabricated by a nanoprecipitation method using poly(dl -lactide-co-glycolide)/poly(ethylene glycol) copolymer. Results Vorinostat-NPs exhibited spherical shapes with sizes <100 nm. Vorinostat-NPs have anticancer activity similar to that of vorinostat in vitro. Vorinostat-NPs as well as vorinostat itself increased acetylation of histone-H3. Furthermore, vorinostat-NPs have similar effectiveness in the suppression or expression of histone deacetylase, mutant type p53, p21, and PARP/cleaved caspase-3. However, vorinostat-NPs showed improved antitumor activity against HuCC-T1 cancer cell-bearing mice compared to vorinostat, whereas empty nanoparticles had no effect on tumor growth. Furthermore, vorinostat-NPs increased the expression of acetylated histone H3 in tumor tissue and suppressed histone deacetylase (HDAC) expression in vivo. The improved antitumor activity of vorinostat-NPs can be explained by molecular imaging studies using near-infrared (NIR) dye-incorporated nanoparticles, i.e. NIR-dye-incorporated nanoparticles were intensively accumulated in the tumor region rather than normal one. Conclusions Our results demonstrate that vorinostat and vorinostat-NPs exert anticancer activity against HuCC-T1 cholangiocarcinoma cells by specific inhibition of HDAC expression. Thus, we suggest that vorinostat-NPs are a promising candidate for anticancer chemotherapy in cholangiocarcinoma.Graphical abstract Local delivery strategy of vorinostat-NPs against cholangiocarcinomas.